Origin of Life: The Point of No Return - Kunnev, Dimiter (Life (Basel, Switzerland), 2020)
Origin of life research is one of the greatest scientific frontiers of mankind. Many hypotheses have been proposed to explain how life began. Although different hypotheses emphasize different initial phenomena, all of them agree around one important concept: at some point, along with the chain of events toward life, Darwinian evolution emerged. There is no consensus, however, how this occurred. Frequently, the mechanism leading to Darwinian evolution is not addressed and it is assumed that this problem could be solved later, with experimental proof of the hypothesis. Here, the author first defines the minimum components required for Darwinian evolution and then from this standpoint, analyzes some of the hypotheses for the origin of life. Distinctive features of Darwinian evolution and life rooted in the interaction between information and its corresponding structure/function are then reviewed. Due to the obligatory dependency of the information and structure subject to Darwinian evolution, these components must be locked in their origin. One of the most distinctive characteristics of Darwinian evolution in comparison with all other processes is the establishment of a fundamentally new level of matter capable of evolving and adapting. Therefore, the initiation of Darwinian evolution is the “point of no return” after which life begins. In summary: a definition and a mechanism for Darwinian evolution are provided together with a critical analysis of some of the hypotheses for the origin of life.